Beyond the Marketing Hype: Analysis of Communication Campaigns of Electric Vehicles Eco-Friendly Image and Battery Waste Concerns - Putra, Aziz Sandy; Fatimah Yasmin Zein; Rizal B. D. Herdian (Jurnal Spektrum Komunikasi, 2024)
Electric Vehicles (EVs) are gaining widespread attention for their environmentally friendly nature and potential to reduce air pollution. As non-renewable fossil fuels deplete, the need for sustainable alternatives like EVs becomes imperative. The EV market emphasizes the cost-effectiveness of electric fuel and extended travel range, despite the initial higher cost of purchasing an EV. In Indonesia, the government encourages EV adoption through subsidies and improved electric refuelling infrastructure, including exempting EV users from the odd-even vehicle license plate rule in Jakarta. To promote EV adoption, brands employ diverse marketing strategies, urging customers to embrace EVs as agents of environmental change. However, the lack of transparency in how EV brands handle nickel-based battery waste, with a limited lifespan, raises environmental concerns. The accumulation of unusable batteries could pose soil pollution risks as EV usage grows. This research aims to explore the environmental implications of battery waste from EVs in Indonesia and analyze how EV brands address these concerns in their marketing communication campaigns. Adopting a cybernetic approach, the study examines the interconnectedness of marketing communication and consumer buying decisions. Qualitative research is utilized, drawing on various EV studies, facts about EV brand communication, and interviews with experts to provide a comprehensive analysis. Although battery waste might not be a pressing issue in Indonesia currently, inadequate waste handling raises potential future concerns about soil and water contamination. Addressing battery waste responsibly is crucial for promoting sustainable EV adoption.